Current Evidence on the Clinical Relevance of Donor-specific Antibodies in Paediatric Liver Transplantation. Issue 6 (June 2021) - Götz, Juliane K.; Kiene, Hella; Goldschmidt, Imeke; Junge, Norman; Pfister, Eva-Doreen; Leiskau, Christoph; Brown, Rachel M.; Immenschuh, Stephan; Baumann, Ulrich
Abstract : ABSTRACT: The clinical impact of donor-specific antibodies (DSA) occurring before or after liver transplantation (LT) against donor-human leucocyte antigen (HLA) on graft outcome is still unclear. We aim to present the current consensus based on recent paediatric LT case series. Compared to kidney transplantation, the liver seems to be less susceptible to antibody-mediated graft damage, which is likely due to protective Kupffer cell activity. The incidence of DSA after liver transplantation is higher in children than in adults. DSA directed against HLA class II molecules, mainly DQ, occur more often. The presence of such anti-class II DSA (DQ/DR), especially of the complement-binding IgG3 subclass, may be associated with endothelial injury, T-cell-mediated rejection (TCMR), inflammation, and fibrosis. Regular DSA-posttransplant monitoring cannot as yet be recommended in routine practice but may be useful in selected cases. Abstract : Supplemental Digital Content is available in the text